Maxillary distraction osteogenesis and a Le Fort I osteotomy for severe maxillary retrognathia in cleft lip and palate: a case report - Fowler Peter V.; Steenberg Leon; Nguyen Tung (Sciendo, 2020)
The correction of severe maxillary retrognathia in patients presenting with a cleft palate is challenging due to the complexity of the orthodontic preparation and the magnitude of the surgical movements required, along with the relatively high risk of relapse.